Wear and friction characteristics of CGRP composite under wet contact condition using two different test techniques - YOUSIF, B; ELTAYEB, N (ELSEVIER SCIENCE SA, 2008)
This paper presents an investigation on wear and friction characteristics of chopped strand mat (CSM) glass fibres 450g/m(2) reinforced polyester (CGRP) composite under wet contact condition against polished stainless steel counterface. The experiments were conducted using two different techniques, Pin-on-Disc (POD) and Block-on-Ring (BOR), which were integrated in a newly developed machine that could carry both techniques running simultaneously against identical counterface characteristics. CGRP composite was tested in two different orientations (parallel and antiparallel), i.e. P-O and AP-O. The effects of test duration (5-30 min), rotational speed (500 and 700 rpm) and applied load (30-100 N) on specific wear rate and friction coefficient were evaluated. Worn surface morphologies of the composite were observed with a scanning electron microscopy (SEM) and the damage features were characterized. The results revealed that CSM glass fibres orientations and test parameters have a significant influence on the wear and frictional characteristics of the composite in both POD and BOR techniques. CGRP in AP-O showed better wear and frictional performance compared to P-0. When the composite was tested using POD, abrasive wear nature was observed on the worn surface in both orientations. Meanwhile, using BOR technique, smoother surface was observed in AP-O. Presence of water assisted to cool the interface and polish the composite surface in the case of BOR. On the other hand, in POD, rough surface was observed on the composite surface in both P-O and AP-O. Additionally, the counterface roughness was increased at all tested condition and highly pronounced in POD when the CGRP was tested in P-O. (C) 2008 Elsevier B.V. All rights reserved.